Control of Dead Stock and Slow-Moving Drugs in the Pharmacy Installation of the Kendari City Regional General Hospital: Dead Stock and Slow-Moving Drugs - Mulyadi Prasetyo; Tasnim Tasnim; Sartini Riski (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Dead stock and slow moving is still one of the main problems in drug management in primary health facilities. Based on the results of initial observations, data was obtained from the Kendari City Hospital which showed that there were 7 drug items with a total number of 2,682 pcs that experienced slow moving and dead stock in 2019-2021. The purpose of this study was to analyze dead stock and slow-moving drugs at the Kendari City Hospital pharmacy installation Methods: This research method is qualitative research using a case study approach, with data analysis using the QSR NVivo 12 application with content analysis techniques. The sample in this study consisted of 6 informants. Results: The results of the study using NVIVO analysis showed the causes of dead stock and slow moving drugsin the pharmaceutical installation of the Kendari City Hospital, namely the pattern of prescribing, planning and control systems. Meanwhile, the control of dead stock and slow-moving drugs in the pharmaceutical installation at Kendari City Hospital consists of storage, hospital policies, communication, control systems, distribution, drug selection and planning. Conclusion: In conclusion, the causes of dead stock and slow moving in Kendari City Hospital are due to prescribing patterns, control systems and planning. As for the control of dead stock and slow-moving drugs in the pharmaceutical installation of the Kendari City Hospital, the ones that have been effective are storage, hospital policies, communication, distribution and selection, while what has not been effective is drug planning and control systems.